2014
DOI: 10.1039/c4tb00128a
|View full text |Cite
|
Sign up to set email alerts
|

A novel nanoassembled doxorubicin prodrug with a high drug loading for anticancer drug delivery

Abstract: A novel doxorubicin (DOX) prodrug (MPEG-b-DOX) was synthesized that reduces the proportion of inactive materials and minimizes drug leak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…As such, we further determined the intercalating efficacy to enable us to compare our DNA TH effectiveness as a cancer drug carrier with other current nanomedicine formulations available. Our result indicated that our DOX intercalating efficacy (or also known as loading efficiency) on the DNA TH was ≈79 wt%, which is slightly higher than the polyethylene glycol based (80 nm) nanomedicine's DOX loading efficiency of 67 wt% . However, our DNA TH showed far superior loading efficiency when compared to many other nanomedicine formulations of the same size.…”
Section: Resultsmentioning
confidence: 67%
“…As such, we further determined the intercalating efficacy to enable us to compare our DNA TH effectiveness as a cancer drug carrier with other current nanomedicine formulations available. Our result indicated that our DOX intercalating efficacy (or also known as loading efficiency) on the DNA TH was ≈79 wt%, which is slightly higher than the polyethylene glycol based (80 nm) nanomedicine's DOX loading efficiency of 67 wt% . However, our DNA TH showed far superior loading efficiency when compared to many other nanomedicine formulations of the same size.…”
Section: Resultsmentioning
confidence: 67%
“…Xu et al reported a novel graft polymer-Dox conjugate with a Dox-loading content as high as 40 wt%, namely, PEG monomethylether-b-poly(methacrylamide tert-butyl carbazate-Dox) (MPEG-b-Dox) ( Figure 6). 156 The MPEG in this conjugate functioned as the hydrophilic part, and methacrylamide tert-butyl carbazate, which was conjugated to Dox via an acid-labile hydrazine bond, acted as the hydrophobic part. The amphiphilic conjugates selfassembled into micelles with average hydrodynamic size of 80 nm.…”
mentioning
confidence: 99%
“…However, the number of researchers exploring this area and developing new approaches has greatly expanded over the last six years as the field of nanomedicine gathered momentum. For instance, Zhong, 55 Zhang, 56 and Xie 57 took advantage of improvements in polymer synthesis to construct their respective self-assembling PDCs. Both the Zhong and Zhang groups utilized reversible addition-fragmentation chain-transfer (RAFT) polymerization to produce polymer backbones with low polydispersity and controlled molecular weight.…”
Section: Macromolecular Sapdsmentioning
confidence: 99%
“…Zhang, on the other hand, synthesized a hydrazide-bearing monomer forming the polymer MPEG-MBAH 6 (methacrylamide Boc-hydrazide). 56 Removal of the Boc protecting group then enabled DOX incorporation through hydrazone formation (Figure 4b). Xie and co-workers used anionic ring opening polymerization (ROP) to create a vinyl-functionalized polymer, PEG- b -PAGE (poly(allyl glycidyl ether)), which was then converted to a carboxylate-bearing polymer for the attachment of PTX (Figure 4c).…”
Section: Macromolecular Sapdsmentioning
confidence: 99%